The Organization of repair addressing problems in understanding in Philippine online multiplayer gaming conversations - Jugan, Jairus B.; Castro, Maria Corazon Saturnina A. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2005)
This study entitled "The Organization of Repair: Addressing Problems in Understanding in Philippine Online Gaming Conversations" investigates how repair mechanisms operate within local online gaming communication. This study also discusses the main types of repairs and initiation using examples taken from chat transcripts. In the process, several strategies of repair and initiation are enumerated and then discussed to further understand how they work. This study demonstrates the adequacy of Conversation Analysis as a method for analyzing the language used in players' interactions. Since the language of online gaming employs generic organizational structures in maintaining conversation, the said approach would help identify underlying principles which help prevent misunderstanding in the online gaming discourse.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.